The Influence of Product Knowledge and Brand Awareness on Purchase Intentions on the Lazada E-Commerce Platform - Ahmad farishin Ikhwan; Ahmad Nuh (Interkoneksi: Journal of Computer Science and Digital Business, 2024)
This research aims to examine the influence of product knowledge and brand awareness on purchase intentions on the Lazada e-commerce platform. Using a quantitative approach, the sample consisted of 400 Lazada consumers who were randomly selected, and data was collected through an online questionnaire covering demographics, product knowledge, brand awareness, purchase intentions, and social influence. Analysis using Structural Equation Models (SEM) shows that product knowledge and brand awareness have a positive and significant influence on purchase intentions. In addition, this research also found that social influence acts as a mediator in the relationship between product knowledge and brand awareness and purchase intention. The results of this research emphasize the importance of product knowledge and brand awareness in increasing customer purchase intentions on the Lazada e-commerce platform, as well as providing important implications for marketers in increasing customer engagement and loyalty in the ever-growing digital market.